Pertanggungjawaban Pidana Anak Sebagai Pelaku Tindak Pidana Pemerkosaan Terhadap Anak Yang Mengakibatkan Cacat Seumur Hidup Dan Kehamilan (Studi Kasus Putusan Mahkamah Agung Nomor 3440 K/Pid.Sus/2019) - Bimasa Zebua; Muhammad Yamin; Adil Akhyar (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
Abstract Acts of decency are all kinds of behavior with sexual connotations that are carried out unilaterally and are not expected by the target person, causing negative reactions, shame, anger, offense at the person who is a victim of sexual harassment. It is concluded that the criminal responsibility of children as perpetrators of the criminal act of rape against children is an effort to protect child victims of the crime of rape because it is one of the crimes against decency as regulated in Article 285 of the Criminal Code, while according to the Criminal Code Bill is regulated in Chapter XVI Concerning the Crime of Morality, Paragraph 1, which reads: